Eye development: stable cell fate decisions in insect colour vision. - Freeman, M (2005)
The retina provides an example of a fundamental property of developing cells: cell fate decisions are stable. A recent paper reports a double negative feedback loop that leads to bistable fate decisions in the colour-detecting photoreceptors of Drosophila.